EVALUASI PELAKSANAAN KURIKULUM 2013 TINGKAT SATUAN PENDIDIKAN DASAR/ SEKOLAH DASAR DI KOTA PEKALONGAN - Matra, Sarlita Dewi; Sidqi, M. Fajru; Ulya, Inayatul (JURNAL LITBANG KOTA PEKALONGAN, 2014)
The research tries to give a thorough description about the implementation of 2013 Curriculum in each element of change which have been implemented by the elementary schools in Pekalongan. Schools’ sample which is used are 1) SD N Medono 08, 2) SD N Podosugih 01, 3) SD N Klego 01, dan 4) SD Islam 01. This research is evaluation research, which took one of the evaluation model namely CIPP model whci is developed by Stufflebeam and descriptive qualititative approach. Some schools have done the schoo l management which is suggested by 2013 curriculum, head master has actively improving school performance and also the teachers in implementing 2013 curriculum in planning stages, teaching process application, and also evaluating periodically. The teachers’ understanding toward the elements of change in 2013 curriculum need to be supported by the good school environment and also school management but majority of teachers in other samples still have difficulties in understanding scientific approach which becomes the charactieristic of 2013 curriculum for applying teaching and learning process in the class in order to make the students active and think critically during the lesson. From the result of the study, it can be suggested that school supervising for head masters either by the education department or the expertieare is very needed to gueode in planning, preparing the document, implementing, and evaluating. The improvement of teachers’ understanding about 2013 curriculum could be done through the teachers’ trainning which effectively should be given for all teachers continuously. Keywords: Evaluation, 2013 Curriculum, CIPP model, Elementary School